HAND GESTURE RECOGNITION USING FUZZY LOGIC WITH COMPUTER STEREO VISION - MARTININGTYAS (NIM : 23207130); Pembimbing I : Dr. Ir. Yudi Satria Gondokaryono; Pembimbing II, FINA
Hand gestures are collection of physical hand movement that have semantic interpretation. Human easly interpert hand gesture. In other side, computer splikasi does not have nature ability to recognize human hand gestures. Stereo vision is 3D information extraction from 2D digital pictures. By compairing two or more pictures from different camera sets, 3D information then collected from difference of prespective from each camera. With stereo vision, hand movement can be represent by vector in 3D space. Fuzzy logic is a mathmetics logic that state the truth is between [0,1] slope. Hand gestures are full of fuzzy state. Fuzzy logic can be use to interpret collection of hand movement captured by stereo vision as hand gesture. This thesis will recognize hand gesture using fuzzy logic interpretation from data collections of hand movement captured by computer stereo vision. Rotate and zoom gesture is what will be recognize. Glove and infra red marker will be use to get data points from collection of hand movement. Fuzzy membership function (fuzzy set) developed with calculation of total kinetic energy. Which rotation and translation movement can be differentiate by its angular and liniear momentum effecting the total energy. Rotate and zoom gesture can be recognize by this approach.